Effects of Pollution on Freshwater Organisms. (1st October 2017) - Choudri, B.S.; Charabi, Yassine; Baawain, Mahad; Ahmed, Mushtauqe
Abstract : This review covers research papers and scientific literature published in the year 2016 on the effects of anthropogenic pollutants on freshwater organisms. In the first, the review begins with two broad sections thate are mainly focused on research reviews and broad field studies and surveys. This is followed by reviews of research categorized in sections to reflect the pollutant class. These sections include wastewater, stormwater and non‐point source pollution, nutrients, sediment cap materials and suspended clays, botanical extracts, surfactants, metals, persistent organic pollutants, pharmaceuticals, endocrine disruptors, pesticides, petroleum hydrocarbons and polycyclic aromatic hydrocarbons (PAHs), ionic liquids, and nanomaterials. The final section of the review highlights the research published on describing innovations in the field of freshwater pollution research.